Analysis of Key Techniques and Application Prospect of Dual Clutch Transmission - Liao Linqing; Ma Anpeng; Zhang Jun; Li Nan (Jixie chuandong)
The dual clutch transmission（DCT） as a kind of new automatic transmission,which integrates the high efficiency of manual transmission and the power gear shift of automatic transmission,and it has become the hot point in the field of world transmission technology.The development history and current situation of DCT are introduced,the structure and operational principle are described in detail as well,and the launching and shifting technology of DCT vehicle are emphatically analyzed.At the same time,forecast the prospect of its development.